The Concept of Nature in Malay Tradition: The Perspective of Islamic Cosmology and Local Wisdom - Niswah, Choirun; Khairunnisah, Alya; Ulya, Ratu Triana; Khotimah, Husnul (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
This study examines the concept of nature within Malay tradition through the lens of Islamic cosmology and local wisdom. The scope of the research focuses on how nature is understood, interpreted, and preserved in Malay culture, which is shaped by Islamic values and indigenous traditions. The objective of this study is to explore the integration between Islamic cosmological perspectives and local wisdom in shaping the Malay worldview toward nature. A descriptive qualitative approach was employed, using literature review methods that draw upon sources related to Islamic cosmology, Malay traditions, as well as ethnographic and cultural documents. The findings reveal that nature in Malay tradition is not merely viewed as a physical entity, but as a sacred part of the spiritual and social order. Nature is regarded as God's creation, deserving of respect and care, as reflected in Islamic values such as tawhid, amanah, and rahmatan lil 'alamin, which are harmoniously integrated with local wisdom expressed through proverbs, natural symbolism, and ecological practices of the Malay community. In conclusion, there exists a synergy between Islamic cosmology and local wisdom that shapes the ecological awareness of the Malay people, offering a holistic and sustainable model of environmental ethics.